A randomized clinical trial comparing basal insulin peglispro and insulin glargine, in combination with prandial insulin lispro, in patients with type 1 diabetes: IMAGINE 11. (10th October 2016) - Garg, S.; Dreyer, M.; Jinnouchi, H.; Mou, J.; Qu, Y.; Hartman, M. L.; Rosilio, M.; Jacober, S. J.; Bastyr, E. J.; ,
Abstract : Aims: The primary objective was to demonstrate that basal insulin peglispro (BIL) was non‐inferior compared with insulin glargine (GL) for haemoglobin A1c (HbA1c) at 26 weeks with a non‐inferiority margin of 0.4%. Materials and Methods: IMAGINE 1 was a Phase 3, open‐label, parallel‐arm study conducted in nine countries. Adults with type 1 diabetes ( n  = 455) were randomized (2:1) to bedtime BIL or GL in combination with prandial insulin lispro for 78 weeks, with a primary endpoint of 26 weeks. An electronic diary facilitated data capture and insulin dosing calculations for intensive insulin management. Results: At 26 weeks, mean HbA1c was 7.06% ± 0.04% and 7.43% ± 0.06% for patients assigned to BIL (N = 295) and GL (N = 160), respectively (difference ‐0.37% [95% CI: −0.50 to −0.23], P  < .001); more patients on BIL achieved HbA1c <7% (44.9% vs 27.5%, P  < .001). Compared with GL, patients using BIL lost weight, with lower fasting serum glucose and between‐day fasting blood glucose variability, and 36% less nocturnal hypoglycemia, 29% more total hypoglycemia and more severe hypoglycemia. Total and prandial insulin doses were lower with BIL; basal insulin doses were higher. Alanine aminotransferase increased with BIL, with more patients having elevations ≥3 × ULN. BIL treatment was associated with more frequent injection site reactions and an increase from baseline in serum triglycerides. Conclusions: In patients with type 1 diabetes, treatment with BIL compared to GL for 26 weeks was associated with lower HbA1c, less nocturnal hypoglycemia, lower glucose variability and weight loss. Increases in total and severe hypoglycemia, triglycerides, aminotransferases and injection site reactions were also noted.